If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -17 = 3x + -105 Reorder the terms: -17 + -8x = 3x + -105 Reorder the terms: -17 + -8x = -105 + 3x Solving -17 + -8x = -105 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -17 + -8x + -3x = -105 + 3x + -3x Combine like terms: -8x + -3x = -11x -17 + -11x = -105 + 3x + -3x Combine like terms: 3x + -3x = 0 -17 + -11x = -105 + 0 -17 + -11x = -105 Add '17' to each side of the equation. -17 + 17 + -11x = -105 + 17 Combine like terms: -17 + 17 = 0 0 + -11x = -105 + 17 -11x = -105 + 17 Combine like terms: -105 + 17 = -88 -11x = -88 Divide each side by '-11'. x = 8 Simplifying x = 8
| e=5n+8 | | 5x^2+8=4x^2-6x | | 25=-16t^2+35t+5 | | 8x^2=980 | | -3(3b+1)-12=12 | | (b^6c^2)-8= | | .20*65=x | | s+s+325000=550000000 | | s+s+32500=550000000 | | 2(2+2y)=19-3y | | s+s+325=550 | | -15-3x=-7x+45 | | F*0=6*0-1 | | 5xn-20=8 | | 14=1.5(7) | | 6(6+68)= | | n+36=56 | | 12s-12=9s-8 | | 6x+6=4x-2 | | 60x-60=144 | | n*5=95 | | 4m^2-227m-40=0 | | n-2=180 | | 3x-2=6+4x | | -24/8 | | s+s+6=214 | | (5x+3)+32=90 | | (x-6)+2x=180 | | -4x-4=2x+8 | | 17-2x=0 | | 6x-5=38 | | (6x+2)+(2x+8)=90 |